Length-dependent conductance of molecular wires and contact resistance in metal–molecule–metal junctions - Liu, Hongmei (2012)
Molecular wires are covalently bonded to gold electrodes—to form metal–molecule–metal junctions—by functionalizing each end with a SH group. The conductance of a wide variety of molecular junctions is studied theoretically by using first-principles density functional theory (DFT) combined with the nonequilibrium Green′s function (NEGF) formalism. Based on the chain-length-dependent conductance of the series of molecular wires, the attenuation factor β is obtained and compared with the experimental data. The β value is quantitatively correlated to the molecular HOMO–LUMO gap. Coupling between the metallic electrode and the molecular bridge plays an important role in electron transport. A contact resistance of 6.0±2.0 KΩ is obtained by extrapolating the molecular-bridge length to zero. This value is of the same magnitude as the quantum resistance.